Penetration and encapsulation of the larval endoparasitoid Exorista larvarum (Diptera: Tachinidae) in the factitious host Galleria mellonella (Lepidoptera: Pyralidae) - Valigurová, A; Michalková, V; Koník, P; Dindo, M L; Gelnar, M; Vaňhara, J (Bulletin of entomological research, 2014)
The tachinid fly Exorista larvarum (L.) (Diptera: Tachinidae) is a polyphagous larval endoparasitoid that deposits its eggs on the host exoskeleton of lepidopteran and tenthredinid larvae. The attachment of larval E. larvarum and the formation of the respiratory funnel were studied during infestation in the last larval instar of the wax moth, Galleria mellonella (L.) (Lepidoptera: Pyralidae). The tachinid larvae burrow through the host integument after hatching, using their robust cephalopharyngeal skeleton, leaving a dark spot at the point of their penetration as a result of host cuticle melanization. Endoparasitoid penetration induces the host cellular defence, resulting in the formation of a haemocyte capsule consisting of multi-cellular sheaths. This enveloping capsule later undergoes melanization, which is mostly obvious towards the posterior part of the endoparasitoid. The endoparasitoid uses the host encapsulation response to build a respiratory funnel from the modified host integument, leading to the host surface. The encapsulated larva remains attached to the respiratory funnel via an anal hook and cuticular spines until fully developed. Additional immunohistochemical analyses were used to study host-parasitoid interactions. Indirect immunofluorescence showed no labelling of potential tachinid antigens and confirmed no effect on the surrounding host tissues. A simulated parasitization with coated polybead microspheres revealed the mortal impact of tachinid antigens to the host. Hosts injected with antigen-coated polybeads died as a consequence of an acute and extensive immunological response to the tachinid antigens and not due to the trauma caused by foreign objects inside their body.
Keywords: myši; Host-Parasite Interactions; Fluorescent Antibody Technique, Indirect; Animals; zvířata; fluorescenční protilátková technika nepřímá; Microspheres; larva; můry; Moths; Female; Diptera; interakce hostitele a parazita; Mice; Larva; mikrosféry; ženské pohlaví